2022
DOI: 10.1542/peds.2021-054677
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Antibiotic Use for Children Hospitalized With Pneumonia

Abstract: BACKGROUND: Antibiotics are frequently used for community-acquired pneumonia (CAP), although viral etiologies predominate. We sought to determine factors associated with antibiotic use among children hospitalized with suspected CAP. METHODS: We conducted a prospective cohort study of children who presented to the emergency department (ED) and were hospitalized for suspected CAP. We estimated risk factors associated with recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Given rising rates of antibiotic resistance, it is critical that we develop and implement evidenced-based practices for the diagnosis and management of pediatric CAP. 29,32,33 We found that hospitals that diagnosed bacterial CAP more there is potential for misclassification bias for patients with an LRTI or bacterial CAP. However, we used definitions derived from prior literature to minimize this limitation.…”
Section: Few Studies Have Evaluated the Proportion Of Children Withmentioning
confidence: 82%
See 1 more Smart Citation
“…Given rising rates of antibiotic resistance, it is critical that we develop and implement evidenced-based practices for the diagnosis and management of pediatric CAP. 29,32,33 We found that hospitals that diagnosed bacterial CAP more there is potential for misclassification bias for patients with an LRTI or bacterial CAP. However, we used definitions derived from prior literature to minimize this limitation.…”
Section: Few Studies Have Evaluated the Proportion Of Children Withmentioning
confidence: 82%
“…It is also important to evaluate how hospital culture may drive some of these practice differences. Given rising rates of antibiotic resistance, it is critical that we develop and implement evidenced‐based practices for the diagnosis and management of pediatric CAP 29,32,33 …”
Section: Discussionmentioning
confidence: 99%
“…We included a practical cohort of children managed in the ED for suspected CAP, regardless of radiographic findings. This is supported by multiple studies demonstrating that CXR interpretation is subjective, antibiotic decisions are made a priori of CXR results, and children can be diagnosed with CAP based on clinical findings even in the absence of radiographic confirmation 13,15–18 . CXRs were initially interpreted based on pediatric radiologists' impressions as part of clinical care.…”
Section: Methodsmentioning
confidence: 99%
“…In a sensitivity analysis, we redefined the exposure as a full antibiotic course (≥5 days inpatient or prescription at discharge), regardless of antibiotic receipt in the ED 19 . We evaluated ED antibiotics as our primary exposure because data suggest that antibiotics started in the ED are frequently continued for a full course 17 and timing between exposure and outcomes. While antibiotic decisions in the ED are typically influenced by a child's initial presentation in the ED, decisions about a full course may be influenced by additional factors that occur after hospital admission (e.g., escalated respiratory support), which were secondary outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation